2017
DOI: 10.1002/imhj.21667
|View full text |Cite
|
Sign up to set email alerts
|

Early Head Start Families’ Experiences With Stress: Understanding Variations Within a High‐risk, Low‐income Sample

Abstract: The federal Early Head Start program provides a relevant context to examine families' experiences with stress since participants qualify on the basis of poverty and risk. Building on previous research that has shown variations in demographic and economic risks even among qualifying families, we examined possible variations in families' perceptions of stress. Family, parent, and child data were collected to measure stressors and risk across a variety of domains in families' everyday lives, primarily from self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…First, we followed Farah's (2017) recommendations on exploring effects of SES in a way that increases comparability across studies by reporting the effects of each SES indicator and their composite score, but prioritizing one indicator in our results. The prioritized indicator was income, because income is the most variable SES indicator that may be more closely associated with different levels of family stress including financial strain (Hustedt et al, 2017;Raver et al, 2015) and has been shown to correlate with children's stress reactivity (Badanes et al, 2011;Kraft & Luecken, 2009; but see Hostinar et al, 2015aHostinar et al, , 2015b. Although the sample's income distribution included 17% of families living below the poverty threshold, which mirrors population statistics for Berlin, parental education and occupational status suggested that higher SES was overrepresented.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, we followed Farah's (2017) recommendations on exploring effects of SES in a way that increases comparability across studies by reporting the effects of each SES indicator and their composite score, but prioritizing one indicator in our results. The prioritized indicator was income, because income is the most variable SES indicator that may be more closely associated with different levels of family stress including financial strain (Hustedt et al, 2017;Raver et al, 2015) and has been shown to correlate with children's stress reactivity (Badanes et al, 2011;Kraft & Luecken, 2009; but see Hostinar et al, 2015aHostinar et al, , 2015b. Although the sample's income distribution included 17% of families living below the poverty threshold, which mirrors population statistics for Berlin, parental education and occupational status suggested that higher SES was overrepresented.…”
Section: Methodsmentioning
confidence: 99%
“…In samples of more moderately varying SES, associations with child cognition are still found (Obradović, Portilla, & Ballard, 2016), but income and education are not as highly correlated and may have diverging associations with child outcomes (Farah et al, 2008;Noble et al, 2015). Those samples may experience different levels of stress related to financial strain (Hustedt et al, 2017;Raver et al, 2015) or other factors correlated with SES (Bradley & Corwyn, 2002), despite being relatively well-educated in socially recognized occupations. Furthermore, income is the most variable SES indicator (Duncan, Ziol-Guest, & Kalil, 2010) and most commonly targeted by policy programs.…”
Section: Measurement Of Ses-related Effectsmentioning
confidence: 99%
See 3 more Smart Citations